Quantitative Analysis of Freestyle Technique - Matos, Carolina; Louro, Hugo; Martynenko, Dmytriy; Melo, Rafael (Revista da UI_IPSantarém, 2020)
One of the main objectives of Biomechanics applied to Sports is to characterize a determined motor pattern and intervene in a way that the motor efficiency is improved. That improvement in efficiency of the motion has, as a final goal, to allow the executant to reach higher levels of performance. The analysis of the variation of speed in a full swimming cycle contributes to the swimmer’s movement and presents a set of information relative to the different phases of the cycle. With this research we went to go beyond the subjective analysis and perform the quantitative analysis. This analysis was performed in a two-dimension space (2D), on the plane perpendicular to the movement in analysis. Three swimmers were analyzed, with this analysis being made in SkillSpector. The conclusion we reached was that there are some differences in swimming with and without breathing, being the latter more beneficial regarding the trunk’s position and the stroke speed.